Predictive Influence of Law Library Resources in Reviewing of Cases: The Case of State and Federal High Courts in Port Harcourt and Enugu Metropolis - Owushi, Emmanuel; Anyalebechi , Okwuchisab Jacinta (International Journal of Knowledge Content Development & Technology, 2025)
This study examines the predictive influence of law library resources in reviewing cases within State and Federal High Courts in Port Harcourt and Enugu metropolis. Employing a survey research design, the population consisted of legal practitioners, law lecturers, law librarians, and law students, with a total sample size of 3,021. Mean score analysis was utilized to assess the responses collected through structured questionnaires. Findings reveal a significant positive influence of law library resources on case review processes, including enhancing thoroughness, improving quality, saving time, and providing invaluable support. However, discrepancies exist in the perceived dependency on resources among legal professionals and researchers. Moreover, challenges affecting the stocking of law libraries with relevant resources were identified, including insufficient funding, limited physical space, difficulties in accessing up-to-date publications, lack of awareness among decision-makers, copyright issues, and inadequate staffing. The study concludes that addressing these challenges, through increased funding, space optimization, improved access to publications, awareness campaigns, and staffing enhancements, is crucial for enhancing the effectiveness of legal research and practice in the studied courts.